Use of Exponential Function in Plant Growth Analysis: A Mathematical Study of Herbal Plants in Nepal - Thakur, Kritika Kumari; Sahani, Suresh Kumar; Thakur, Ambika Kumari; Sahani, Kameshwar; Prasad, Nayan Kumar; Sah, Binod Kumar (Lembaga Yasin AlSys, 2024)
Plants are the reason why we all human beings or living beings are alive. We are nothing without plants. We Nepalese are lucky that we don’t only have a large variety of plants but also many more rare plants which are not easily found all over the world. Some of the rare plants are Rhododendron, Jatamanshi, Yarshagumba, etc. which not only have medicinal importance but also are very expensive. Above 80% crude herbs are exported to India, China and other countries. But one of the saddest things is Nepal hasn’t yet become one of the most popular or largest countries to export herbs. Maybe because we are surrounded by land. But there are various geographical importance of Nepal. We should consider it and extend the export rate. Nepal is rich in medicinal plants and aromatic plants, from Terai to Himalayan region. Due to the geography, Nepal. Consists of some of the unbelievable medicinal herbs which can cure various diseases. In this project I have discussed some of the precious herbal plants found in Nepal.